共轭亚麻酸的生理功能及制备方法研究进展Research progress in physiological function and preparation method of conjugated linolenic acid - 鲍雅婷1，赵瑶瑶2，郑洲1，缪锦来1 BAO Yating1, ZHAO Yaoyao2, ZHENG Zhou1, MIAO Jinlai1 (Zhongguo youzhi, 2024)
旨在为共轭亚麻酸（CLNA）在功能食品、保健品和药品等领域的应用提供科学的理论参考，综述了CLNA的生理功能和制备方法。CLNA具有抗癌、调节脂质代谢、抗炎、抗氧化、抗糖尿病等多种生理功能，在预防和治疗许多常见疾病中具有较大的研究潜力，特别是糖尿病、肥胖症以及乳腺癌、结肠癌等常见癌症。物理提取法制备CLNA时提取率较低，不适用于工业上大规模生产，化学合成法制备CLNA因需要底物和催化剂，后续纯化步骤烦琐，生物合成法和基因工程法可得到较高含量的CLNA，具有良好的发展前景。In order to provide scientific theoretical reference for the application of conjugated linolenic acid (CLNA) in the fields of functional foods, health products and medicines, the physiological function and preparation method of CLNA were reviewed.CLNA has a variety of physiological functions such as anti-cancer, regulating lipid metabolism, anti-inflammatory, anti-oxidation, anti-diabetic and so on. CLNA has great potential in the prevention and treatment of many common diseases, especially diabetes, obesity, and common cancers such as breast cancer and colon cancer. The extraction rate of CLNA prepared by physical extraction method is low, and it is not suitable for large-scale production in industry. Due to the need of substrates and catalysts, the subsequent purification step of the preparation of CLNA by chemical synthesis method is cumbersome. The microbial method and genetic engineering method can obtain a higher content of CLNA, so it has a good prospect for development.